Tracking Maternal and Child Anthropometric Outcomes, Early Childhood Development, Maternal Mental Health and Household Welfare in urban Yangon and rural Ayeyarwady: A Description of the 11th Round of The Rural-Urban Food Security Survey (RUFSS) conducted in October-November 2023 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
Myanmar's population has become increasingly at risk of malnutrition due to political turmoil, armed conflicts, the COVID-19 pandemic, economic disruptions, price fluctuations, and erratic weather patterns (MAPSA 2024; MAPSA 2023). However, given the fragile situation with respect to conflict, crime and poor governance, conducting face-to-face data collection is challenging (Lambrecht et al. 2023; Boughton et al. 2023), and there is a particular scarcity of anthropometric data since this cannot be collected via phone surveys. To redress this knowledge gap, IFPRI partnered with Innovations for Poverty Action (IPA)- Myanmar to conduct an in-person survey that revisited households previously surveyed in 2020-2021 by phone. This Rural-Urban Food Security interviewed mothers or caregivers of young children and collected anthropometric measurements in-person between October – November 2023. Out of approximately 1,500 mothers who participated in at least one round of the previous phone survey, we successfully followed up with 702 mother-child pairs located mainly in peri-urban Yangon, with a small subset of households in rural Ayeyarwady. This paper describes the implementation of this survey and the reports key results from the questionnaire in order to provide readers with a clear understanding of the sample and its key socioeconomic characteristics, as well as comparability to two national surveys with representative Yangon sub-samples: the Myanmar Household Welfare Survey (MHWS) conducted in 2023 and Demographic and Health Survey (DHS) conducted in 2015-16. Results of this comparison suggest that the RUFSS sample of caregivers (mostly mothers) is broadly comparable to the DHS in terms of education levels. Thus, while the RUFSS sample should not be interrupted as representative of mothers of young children in Yangon or their households – because we oversample peri-urban households – it nevertheless appears to be broadly comparable to the DHS in terms of caregiver education levels, which would one not expect to change rapidly over 2015-16 to 2023.